Influences of listeners' native and other dialects on cross-language vowel perception - Williams, Daniel; Escudero, Paola (Frontiers in Psychology, 2014)
This paper examines to what extent acoustic similarity between native and non-native vowels predicts non-native vowel perception and whether this process is influenced by listeners’ native and other non-native dialects. Listeners with Northern and Southern British English dialects completed a perceptual assimilation task in which they categorized tokens of 15 Dutch vowels in terms of English vowel categories. While the cross-language acoustic similarity of Dutch vowels to English vowels largely predicted Southern listeners’ perceptual assimilation patterns, this was not the case for Northern listeners, whose assimilation patterns resembled those of Southern listeners for all but three Dutch vowels. The cross-language acoustic similarity of Dutch vowels to Northern English vowels was re-examined by incorporating Southern English tokens, which resulted in considerable improvements in the predicting power of cross-language acoustic similarity. This suggests that Northern listeners’ assimilation of Dutch vowels to English vowels was influenced by knowledge of both native Northern and non-native Southern English vowel categories. The implications of these findings for theories of non-native speech perception are discussed.